Correlation-Based Search against Friendly Jamming Data Exchange Schemes - Zhang, Jingyi; Hu, Qiao; Hancke, Gerhard Petrus (2019 IEEE Conference on Dependable and Secure Computing (DSC), 2019)
Friendly jamming is a physical-layer approach to protecting the confidentiality of short range wireless communication. In recent years, several practical friendly jamming scenes have been proposed based on the general principle that the recipient jams the channel while the data is being sent by another party. However, the security analysis of these schemes is a tricky subject, with works often showing that the scheme is secure against a specific implementation of a passive attacker or multiple attackers. These attackers are often modeled as conventional receivers, but interesting questions can be raised about whether there are better or new methods for attackers to use to recover jammed data. This paper introduces a signal correlation-based message recovery method against friendly jamming. Using this method a single eavesdropper is able to recover large parts of the secret message under the condition which is assumed to be secure enough by previous practical friendly jamming schemes. We analyze the impact of factors on our attack such as start positions, relation thresholds, the length of the section signals and plaintext by simulation. Results of experiment attacking an acoustic friendly jamming system indicative of this approach shows a much lower SNR upper threshold.